PENGARUH PASTRY EQUIPMENT TERHADAP KUALITAS PASTRY PRODUCT DI HOTEL PANGERAN PEKANBARU - Siti Masitoh; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Patisserie (Pastry And Bakery) is a product that is produced through various processes in the form of cakes and breads. Patisseries products are usually made based on available formulas or recipes, in addition to recipes and raw materials, pastry equipment and supplies also have a very important role in supporting the success of pastry products at Pangeran Hotel Pekanbaru. This research was conducted with the aim of knowing the effect of pastry equipment on the quality of pastry products at Pangeran Hotel Pekanbaru. Pastry equipment is a very important based on its factors in the production process. Pastry Equipment based on its function is divided into 6 groups, namely storage equipment, decorating equipment, baking equipment, measuring equipment, supporting equipment, medium & heavy equipment. While product quality is how the product has a value that can satisfy consumers both physically and psychologically which shows the attributes or properties contained in an item or result. This study uses a quantitative method with a descriptive approach. Data collection technique in this study using observation, questionnaires, literature study and interviews so as to get a clear picture. The informants in this study were pastry chefs and 91 respondents. From this study, it was found that there was no significant effect of pastry equipment on a quality of pastry products at Hotel Pangeran Pekanbaru. Keywords : Effect, Pastisserie, pastry Equipments, Product Quality